2014
DOI: 10.1016/j.mehy.2014.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Pressure waves in neurons and their relationship to tangled neurons and plaques

Abstract: The paper based on the hypothesis that mechanical impulses cause the transmission of excitement in the peripheral and central nervous system. Possible connections between changes in the tubular neuronal network and the morphological findings of Alzheimer's disease are presented. Additionally, changes in the viscosity of the neuronal cytoplasm and changes in the walls of the neuronal fibers due to the intracellular hydrostatic pressure and pressure waves are considered possible causes of plaques, threads and ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In what follows, an attempt is described following the ideas of Andersen et al [2] to build up a mathematical model which could account for main effects in signal propagation in nerve fibres. Based on classical understandings of axon physiology [9,12], the following basic assumptions are made: (i) electrical signals are the carriers of information [12] and trigger all the other processes; (ii) the axoplasm in a fibre can be modelled as fluid where a pressure wave is generated due to electrical signal; here, for example, the actin filaments in the axoplasm may influence the opening of channels in the surrounding biomembrane but do not influence the generation of pressure wave in the fluid [2]; (iii) the biomembrane is able to deform (stretch, bending) under mechanical impact [24]; (iv) the channels in biomembranes can be opened and closed under the influence of electrical signals as well as of the mechanical input; it means that tension of a membrane leads to the increase of transmembranal ion flow and the intracellular actin filaments may influence the motions at the membrane [4,32]; (v) there is strong experimental evidence on electrical or chemical transmittance of signals from one neuron to another [5,26] although the role of mechanical transmission is also discussed [3].…”
Section: Assumptions In Modellingmentioning
confidence: 99%
“…In what follows, an attempt is described following the ideas of Andersen et al [2] to build up a mathematical model which could account for main effects in signal propagation in nerve fibres. Based on classical understandings of axon physiology [9,12], the following basic assumptions are made: (i) electrical signals are the carriers of information [12] and trigger all the other processes; (ii) the axoplasm in a fibre can be modelled as fluid where a pressure wave is generated due to electrical signal; here, for example, the actin filaments in the axoplasm may influence the opening of channels in the surrounding biomembrane but do not influence the generation of pressure wave in the fluid [2]; (iii) the biomembrane is able to deform (stretch, bending) under mechanical impact [24]; (iv) the channels in biomembranes can be opened and closed under the influence of electrical signals as well as of the mechanical input; it means that tension of a membrane leads to the increase of transmembranal ion flow and the intracellular actin filaments may influence the motions at the membrane [4,32]; (v) there is strong experimental evidence on electrical or chemical transmittance of signals from one neuron to another [5,26] although the role of mechanical transmission is also discussed [3].…”
Section: Assumptions In Modellingmentioning
confidence: 99%
“…Some explaination is still needed on how the brain takes advantage of pressure waves, temperature and concentration gradients to allow the renewal of the extra-cellular fluid, as well as some forms of intercellular communications at an energy cost way lower than the well-established synaptic transmission [1]. One alternative discusses solitons in the context of mechanical dislocations and temperature changes [25,23,24], while others suggested an axoplasmic pressure pulses [43,4], or electromagnetic pulses [49]. In fact, many studies have shown that a mechanical displacement of the axonal membrane accompanies the electrical pulse which has been used to define an action potential, but there is little theoretical consensus for the physical basis of such waves or their links with the electrical pulse.…”
Section: Introductionmentioning
confidence: 99%